Adaptasi Masyarakat Pendatang Di Kampung Inggris: Komunikasi dan Upaya Pencegahan Disintegrasi - Sholihin, Muhammad Anas; Rifa'i, Akhmad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article discusses how the adaptation of migrant communities in English Village Pare, to find the communication patterns used in efforts to prevent disintegration. Tulungrejo Hamlet, Pare Subdistrict, Kediri Regency known as English Village is a center for the development of foreign language learning that is busy being a reference for immigrant communities. This research uses a Sociological Approach to Structural Functionalism coined by Talcott Parson known as AGIL theory. This research aims to find out how immigrant communities adapt in Kampung Inggris. To achieve this goal, researchers used a qualitative approach with several research methods, including in-depth interviews, documentation, and field research. From the results of the research, there are several results found in efforts to prevent disintegration, including interpersonal communication, mass communication, group communication, and community activities that play a role in preventing disintegration. This research is expected to be able to create good communication, especially between immigrant and local communities to be more able to apply integration to create a good relationship between the two.